Investigating the application of IT generated data as an indicator of learning and teaching performance. - Dawson, Shane; McWilliam, Erica (Australian Learning and Teaching Council, 2008)
Report from a project that aimed to address the need for higher education institutions (HEIs) to develop and adopt scalable and automated measures of learning and teaching performance in order to evaluate the student learning experience. In so doing, the research project presents an evaluative methodology drawing upon data mining techniques and social network research to apply Information and Communication Technology (ICT) to better understand the impact of implemented learning and teaching practices. [Executive summary, ed]